Oral bullous pemphigoid induced by gabapentin: a case report / Mohd Aizuddin Abd Rahman and Mohd Shaiful Ehsan Shalihin - Abd Rahman, Mohd Aizuddin; Ehsan Shalihin, Mohd Shaiful (Faculty of Medicine, 2023)
Drug eruptions typically present with maculapapular rashes and blisters over the body and trunk. Gabapentin was rarely associated with bullous pemphigoid however, the link is still possible, involving localized oral lesions in which oral inspection is indeed essential. We reported a rare case of gabapentin induced oral bullous pemphigoid in an elderly patient who presented with localized lips and gums swelling. The association with gabapentin was almost missed due to the atypical presentation. We ceased the drug immediately. His condition improved by co-management with a dermatologist and application of high dose topical steroid. This case highlighted the importance of adequate history taking, thorough physical examination and immediate management of acute dermatological cases which can save the patient's life.